HISTORICAL-GEOGRAPHICAL ASPECTS OF SUSTAINABLE DEVELOPMENT OF SMALL TOWNS (ON THE EXAMPLE OF SMALL TOWNS IN ZHAMBYL REGION) (Journal of Geography and Environmental Management, 2023)
The problems of sustainable development of small towns were analyzed from the perspective of historical-geographical factors in this article. During the analysis, we were convinced that monoprofile towns, which are part of the group of small towns, have become the "center" of problems in the world and the country. Theoretical and conceptual analysis of the concepts, names, opinions and conclusions of scientists developed in relation to these cities associated with global industrialization was carried out. The main mechanisms of rehabilitation and support of labor resources in monoprofile towns in a crisis situation were determined on the basis of the experience of the USA, Canada, Australia, Japan, Germany and other countries. And in the conditions of our country, we considered on the example of small towns in  Zhambyl region. According to it, the historical aspects of specialization of small towns were given importance, classification of common issues limiting sustainable development was compiled. Demographic problems in towns were analyzed, and the place at the strategic stage of the development of innovative city was determined on the basis of historical data and theoretical conclusions. According to the concept of sustainable development, the main areas of urban environment development were selected, and their social, economic and environmental effects were emphasized. In general, the results of the study in the article will complement research in the field of urban geography.
Keywords: the problem of small and monotowns, town-building enterprises, social modernization, economic diversification, sustainable development.